Synthesis and assessment of the cytotoxic effect of some of 1,4-dihydropyridine derivatives which contain azole moiety - Ghoorbannejad Saeed (Serbian Chemical Society, 2021)
A number of 1,4-dihydropyridine derivatives (9a–d, 10a–d and 11a–d) were designed and synthesized by the reaction of 1,3,4-oxadiazole-5-thiones and 1,2,4-triazole-5-thiones to 2,6-dibromomethyl-3,5-diethoxycarbonyl-4-(3- -nitrophenyl)-1,4-dihydropyridine. The synthesized compounds were characterized using FT-IR, 1H-NMR, 13C-NMR spectral data, ESI-MS and elemental analysis. The cytotoxicity of the synthesized compounds was evaluated in human breast cancer (MCF-7) cells based on the results of MTT assay. The results indicated that compound diethyl 4-(3-nitrophenyl)-2,6-bis[((5-(3-nitrophenyl)- 1,3,4-oxadiazol-2-yl)thio)methyl]-1,4-dihydro pyridine-3,5-dicarboxylate (9b) with (IC50 = 23±2.32 μM) was the most potent derivative against MCF-7 cells. Based on the results, the use of oxadiazole moiety in the C2 and C6 positions of 1,4-dihydropyridine ring system enhanced the cytotoxic potential of these derivatives. Therefore, some of the oxadiazole-substituted 1,4-DHPs may facilitate further modifications which result in the discovery of potent cytotoxic agents.